Continuous Improvement : Vision, Implementation, and Strategy of the Ministry of Education, Culture, Research, and Technology Regulation Number 53 of 2023 on Quality Assurance of Higher Education towards Graduate Competency Standards at Universitas Negeri Semarang - Widodo, Mulyo; Setiyawan, Wahyu Beny Mukti; Mursidah, Siti; Al-Ghin, Majora Nuansa; Khunaefi, Muhammad Wildan (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Previous studies have often focused on meeting the standards set by the government, such as national standards for higher education. However, many of these studies do not present challenges in implementing these policies effectively. Therefore, this study emerged to fill the void of space with a continuous improvement approach. Taking a case study at Semarang State University (UNNES), this study will aim to test the alignment of UNNES recotr regulations on UNNES education standards in 2023, with Permendikbudristek Number 53 of 2023. Using qualitative research methods, this study found that UNNES is adapting itself to the new requirements set by national regulations. Not only that, UNNES is seen to partially answer the challenges that arise with a continuous improvement pattern. As a result, the vision, mission, and strategy of UNNES are in general line with Permendikbudristek Number 53 of 2023. The new findings from this study emphasize the importance of UNNES or other universities to continue to improve their educational process with a continuous improvement approach. The goal is that the national standards that have been set can be implemented in detail in order to achieve Indonesia's educational goals.